Complete lumbarization with calcified disc herniations at L5S1 and S1-2 levels treated with percutaneous endoscopic interlaminar discectomy: a case report and technique note - Lisheng, Hou; Feng, Ge; Dong, Zhang; Tianjun, Gao; Shaokui, Nan; Xuedong, Bai; Qing, He (Frontiers in Surgery, 2023)
Objective This study aims to report a case of a patient with complete lumbarization (Castellvi-IB) who developed symptomatic calcified disc herniations at L5S1 and lumbarized S1-2 levels and achieved excellent neurological recovery following percutaneous endoscopic interlaminar discectomy (PEID). Summary of Background Data In 1984, Castellvi et al. classified lumbosacral transitional vertebra (LSTV) into four types. They incorrectly classified I LSTV anomalies as only type I sacralization, not realizing type I lumbarization also belonged to type I LSTV, with the latter exhibiting a well-developed S1-2 disc (lumbosacral transitional disc, LSTD). Patients with type I lumbarization rarely develop calcified disc herniations concomitantly at L5S1 and LSTD levels. PEID has been developed to perform discectomy for neurological decompression at the lumbar region, especially at the lowest level where the higher iliac crest and/or widened transverse process exists. Methods A 47-year-old male presented to our hospital complaining of an intractable left leg radiating pain for 3 weeks after suffering from chronic radiating pain for 4 years. His physical examination found hyperalgesia at the lateral side of the left calf, decreased dorsal flexion strength of the ankle (grade 4/5), and a positive sign of straight leg raising test at the left side (30°). The preoperational Lumbar JOA (Japanese Orthopaedic Association) score was 12. Image examinations including whole spinal radiograph, MRI, and CT confirmed complete lumbarization (Castellvi-IB) with calcified disc herniations at L5S1 and LSTD levels at the left side. PEID was carried out at two index levels to accomplish decompression via the left approach. Results The patient’s neurological function recovered quickly. One day postoperatively, he began to walk without discomfort. After 3 months, his muscle strength recovered to normal, and after 6 months, the residual dysesthesia at his posterolateral calf disappeared. The follow-up Lumbar JOA score was 26. Conclusion Calcified lumbar disc herniation could develop at two distal levels concomitantly in the case of type I complete lumbarization. This anomaly might be misinterpreted as a normal lumbar sequence by only lumbar MRI. PEID may be an effective procedure to treat such calcified disc herniations in a single visit.